A Gestão do Fitness no Solinca Health & Fitness Rio Tinto - Francisco André Velho Couto (2019)
This report has been drawn up as a part of a professional internship at Solinca's Rio Tinto gym in order to get the master degree in Sports Management by the Faculty of Sports of University of Porto. The internship was established as a good option, since it is a credible company with a margin of internal progression, coupled with the fact that the location of the gym was suitable for me. The aim of the internship was to apply the theoretical knowledge acquired during the first year of the master in a professional context, benefiting from a first contact with the world of fitness and viewing the experience as a possible job opportunity. This report is intended to describe, in a clear and concise way, the activities, moments, challenges, difficulties and achievements throughout the practice of the internship. A literature review is also carried out on the state of knowledge of fitness and its management domains that lead to a better understanding of the area under study. The work developed was particularly more focused on an operational perspective rather than a more strategic and management vision, although this was not the ideal path. The work carried out in the four departments - club manager, membership, commercial consultant and reception - of Solinca Rio Tinto was followed, albeit with different degrees of depth, for a richer experience, starting with the position of membership and then integrating the remaining ones with valences which gave me autonomy. As a result, the skills acquired were more in terms of customer relations, involving their integration and capitation with the gym, as well as qualification and familiarization with the chain's operating system. In conclusion, it was an internship that fulfilled the goals, without, however, exceeding the expectations created.